2022
DOI: 10.5664/jcsm.9658
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Pittsburgh Sleep Quality Index among frontline COVID-19 health care workers using classical test theory and item response theory

Abstract: Study Objectives: The applicability of sleep-related scales to frontline medical staff for the COVID-19 pandemic has not been fully proved, so sleep survey results lack credibility and accuracy, creating difficulties for the guidance and treatment of frontline medical staff with sleep disorders, which is not conducive to the prevention and control of COVID-19. This study sought to analyze the reliability and validity of the Pittsburgh Sleep Quality Index (PSQI) among frontline medical staff fighting the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The global PSQI score, which ranges from 0 to 21, is then calculated by adding the seven component scores; higher numbers denote poorer sleep quality ( 40 ). Numerous investigations have utilized this scale, which has been found to have high reliability and validity ( 41 ). In this study, the Kronbach α coefficient of PSQI was 0.757, the KMO value was 0.741, and the significance of the Bartlett sphericity test was p < 0.001, which indicated good reliability and validity of PSQI.…”
Section: Methodsmentioning
confidence: 99%
“…The global PSQI score, which ranges from 0 to 21, is then calculated by adding the seven component scores; higher numbers denote poorer sleep quality ( 40 ). Numerous investigations have utilized this scale, which has been found to have high reliability and validity ( 41 ). In this study, the Kronbach α coefficient of PSQI was 0.757, the KMO value was 0.741, and the significance of the Bartlett sphericity test was p < 0.001, which indicated good reliability and validity of PSQI.…”
Section: Methodsmentioning
confidence: 99%
“…The Chinese version of the PSQI was translated by Liu [23] in 1996. It has been subsequently applicated in different populations, including those with blood disorders, [24][25][26][27][28] and all indicate the Chinese version is a reliable and valid instrument for assessing sleep quality. In this study, the PSQI showed a fair Cronbach's alpha value of 0.693.…”
Section: Methodsmentioning
confidence: 99%
“…However, the HPSQI assesses sleep-related quality of life (QoL) using seven questions assessed on a 5-points Likert scale to provide a comprehensive measure of daytime functioning, while the PSQI uses only two. Previous research has questioned the validity of the PSQI daytime dysfunction subscale and noted that it did not provide a clear distinction between sleep problems and daytime functioning [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%